Cytokine Storm-Induced Thyroid Dysfunction in COVID-19: Insights into Pathogenesis and Therapeutic Approaches - Attiq A; Afzal S; Wahab HA; Ahmad W; Kandeel M; Almofti YA; Alameen AO; Wu YS (Dove Medical Press, 2024)
Ali Attiq,1 Sheryar Afzal,2 Habibah A Wahab,1 Waqas Ahmad,1 Mahmoud Kandeel,2,3 Yassir A Almofti,2,4 Ahmed O Alameen,2,5 Yuan Seng Wu6,7 1School of Pharmaceutical Sciences, Universiti Sains Malaysia, Gelugor, Penang, 11800, Malaysia; 2Department of Biomedical Sciences, College of Veterinary Medicine, King Faisal University, Al Ahsa, 31982, Saudi Arabia; 3Department of Pharmacology, Faculty of Veterinary Medicine, Kafrelsheikh University, Kafrel Sheikh, 6860404, Egypt; 4Department of Biochemistry, Molecular Biology and Bioinformatics, College of Veterinary Medicine, University of Bahri, Khartoum, 12217, Sudan; 5Department of Physiology, Faculty of Veterinary Medicine, University of Khartoum, Shambat, 13314, Sudan; 6Sunway Microbiome Centre, School of Medical and Life Sciences, Sunway University, Subang Jaya, Selangor, 47500, Malaysia; 7Department of Biological Sciences, School of Medical and Life Sciences, Sunway University, Subang Jaya, Selangor, 47500, MalaysiaCorrespondence: Sheryar Afzal, Department of Biomedical Sciences, College of Veterinary Medicine, King Faisal University, Al Ahsa, 31982, Saudi Arabia, Email safzal@kfu.edu.sa Ali Attiq, School of Pharmaceutical Sciences, Universiti Sains Malaysia, Gelugor, 11800, Penang, Malaysia, Email aliattiq@usm.myAbstract: Angiotensin-converting enzyme 2 receptors (ACE2R) are requisite to enter the host cells for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). ACE2R is constitutive and functions as a type I transmembrane metallo-carboxypeptidase in the renin-angiotensin system (RAS). On thyroid follicular cells, ACE2R allows SARS-CoV-2 to invade the thyroid gland, impose cytopathic effects and produce endocrine abnormalities, including stiff back, neck pain, muscle ache, lethargy, and enlarged, inflamed thyroid gland in COVID-19 patients. Further damage is perpetuated by the sudden bursts of pro-inflammatory cytokines, which is suggestive of a life-threatening syndrome known as a "cytokine storm". IL-1β, IL-6, IFN-γ, and TNF-α are identified as the key orchestrators of the cytokine storm. These inflammatory mediators upregulate transcriptional turnover of nuclear factor-kappa B (NF-κB), Janus kinase/signal transducer and activator of transcription (JAK/STAT), and mitogen-activated protein kinase (MAPK), paving the pathway for cytokine storm-induced thyroid dysfunctions including euthyroid sick syndrome, autoimmune thyroid diseases, and thyrotoxicosis in COVID-19 patients. Targeted therapies with corticosteroids (dexamethasone), JAK inhibitor (baricitinib), nucleotide analogue (remdesivir) and N-acetyl-cysteine have demonstrated effectiveness in terms of attenuating the severity and frequency of cytokine storm-induced thyroid dysfunctions, morbidity and mortality in severe COVID-19 patients. Here, we review the pathogenesis of cytokine storms and the mechanisms and pathways that establish the connection between thyroid disorder and COVID-19. Moreover, cross-talk interactions of signalling pathways and therapeutic strategies to address COVID-19-associated thyroid diseases are also discussed herein.Keywords: COVID-19, cytokine storm, signalling pathways, inflammation, thyroid disorders, cross talks